Działania Organizacji Narodów Zjednoczonych na rzecz dekolonizacji i pokoju w Saharze Zachodniej - Skuczyński, Maciej (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The author examines the role of the United Nations in process of decolonisation of the Western Sahara. The article describes a modern history of Western Sahara focusing on the UN’s policies and activities related to this basing on resolutions, reports and other documents of the organization. The aim of the article is to present UN’s decolonisation and conflict resolution activities in Western Sahara. The text shows that the UN has remarkable achievements concerning the people of Sahara, although the main aim – self-determination of Sahrawi people by referendum – currently is unattainable because of idleness of great powers and firm stance of occupying state – the Kingdom of Morocco.